Biometrics, physiology, production, and quality of Cantaloupe melons grown with saline waters under semi-arid conditions - Lima, Reivany Eduardo Morais; Araújo, Laíse F; Farias, Luciana F. de L.; Bezerra, Marlos A (Comunicata Scientiae, 2020)
Brazilian Northeast region emerges as both producer and exporter relevant of cantaloupe melon to several countries; however, this region is vulnerable to salinization problems due to it is inserted in a semi-arid area. This study aimed to evaluate the biometrics, physiological, production and quality of new cantaloupe melon hybrids cultivated with different saline waters under semi-arid conditions. The experiment was conducted using a drip irrigation system in a split-plot randomized design. The plot was different irrigation water electrical conductivity (ECw) levels: 0.5, 2.0, 3.5, and 5.0 dS m-1, while the subplot was two new cantaloupe melon hybrids: Zielo and SV1044. Plant biometrics (stems and leaves analysis), plant physiology (solutes accumulation and gas exchange in leaves), fruit production (number, weight, and yield), and fruit quality (physical and chemical analysis) were investigated. Stem length, leaf numbers, leaf area, and shoot dry mass decreased when ECw increased from 0.5 to 5.0 dS m-1. Also, there was an increase of Na and Cl concentration and reduction of K concentration in leaves due to ECw increase. Gas exchange reduction, losses in fruit numbers, weight, yield, and in quality were observed with the ECw increase. It is possible to conclude that the ECw increase salinizes the soil and increases Na and Cl concentration in plants causing reduction in gas exchange, in growth, and in fruit production and quality. However, the response of cultivated hybrids regarding salinity may be different, as in our study that the Zielo hybrid was less affected by the increase in ECw.